KOMPARASI ANTARA TEORI BELAJAR DALAM AL-QUR’AN DAN TEORI BARAT MODERN - Khairan M Arif (Akademika, 2016)
Learning theory is a theory that discusses how human beings learn, discussion of learning theoryhas been described in the Qur'an far before the advent of the modern learning theory.The purpose of this study is to provide information and scientific facts how the Qur'an describes humanlearning and how the concept of the Qur'an about studying, so that muslim scholars know the conceptsand principles learned in Islam in particular the Qur'an.The Methods research in this paper is to use the methods of the study of literature and historicalstudy of the theories and concepts in the Qur'an.The results of this study was to reveal exactly how the principles learned in the Qur'an, the humanattitude towards learning, man is a creature of the learners, learning objectives, learning resourcesand learning functions